Biotechnological uses of enzymes from psychrophiles - Cavicchioli, R; Charlton, T; Ertan, H; Mohd Omar, Suhaila; Siddiqui, K S; Williams, T J (Wiley-Blackwell Publishing Inc., 2011)
The bulk of the Earth's biosphere is cold (e.g. 90% of the ocean's waters are ≤ 5°C), sustaining a broad diversity of microbial life. The permanently cold environments vary from the deep ocean to alpine reaches and to polar regions. Commensurate with the extent and diversity of the ecosystems that harbour psychrophilic life, the functional capacity of the microorganisms that inhabitat the cold biosphere are equally diverse. As a result, indigenous psychrophilic microorganisms provide an enormous natural resource of enzymes that function effectively in the cold, and these cold-adapted enzymes have been targeted for their biotechnological potential. In this review we describe the main properties of enzymes from psychrophiles and describe some of their known biotechnological applications and ways to potentially improve their value for biotechnology. The review also covers the use of metagenomics for enzyme screening, the development of psychrophilic gene expression systems and the use of enzymes for cleaning.